2024
DOI: 10.1108/jabs-06-2023-0219
|View full text |Cite
|
Sign up to set email alerts
|

Do selected board governance mechanisms strengthen the link between institutional and macroeconomic variables and the financial flexibility of corporations? Empirical evidence from an emerging economy

Harshani Shashikala Wijerathna,
Niluka Anuradha,
Roshan Ajward

Abstract: Purpose This study aims to explore the relationship between institutional and macroeconomic factors and corporate financial flexibility while also investigating the moderating impact of selected board governance mechanisms on this relationship. Design/methodology/approach The sample of the study comprises 174 firms listed on the Colombo Stock Exchange for a period of eight years, from 2014 to 2021. Data were collected from secondary sources, and both descriptive and inferential statistical techniques were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Either they have focused on companies in a single sector [22] or only listed companies [21]. Most importantly, however, the list of macroeconomic variables considered in the studies was limited and focused on a few basic macroeconomic variables, such as GDP or its growth, inflation, unemployment, or interest rates [19,20,23]. This constitutes an important research gap that the present study was designed to fill.…”
Section: Literature Review and Research Questionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Either they have focused on companies in a single sector [22] or only listed companies [21]. Most importantly, however, the list of macroeconomic variables considered in the studies was limited and focused on a few basic macroeconomic variables, such as GDP or its growth, inflation, unemployment, or interest rates [19,20,23]. This constitutes an important research gap that the present study was designed to fill.…”
Section: Literature Review and Research Questionsmentioning
confidence: 99%
“…Studies on the impact of macroeconomic variables on cash holdings have typically focused on a limited set of macroeconomic variables. However, some of these studies have indicated that the role of macroeconomic factors in relation to liquidity is significant [19,20]. A study by Dottori and Micucci [18] indicated that the increase in the liquidity levels of Italian firms between 2011 and 2015 was mainly due to macroeconomic factors, such as the fall in interest rates.…”
Section: Literature Review and Research Questionsmentioning
confidence: 99%
See 3 more Smart Citations